An English Writing Materials Analysis Through Microlearning Skill Views - Herdian, Irvan; Dewanti, Ratna; Drivoka Sulistyaningrum, Siti (International Journal of Educational Research & Social Sciences, 2023)
Microlearning is a short-term learning strategy that can increase students' interest in learning. It is in line with the characteristics of today's students who cannot focus on learning for long periods of time. The study was conducted at three senior high schools in Bogor, Indonesia. This study aimed to analyze microlearning in writing English learning materials for the tenth grader. This research employed a content analysis approach. The data sources are learning materials from two student books from two publishers that refer to Kurikulum Merdeka Belajar as well as additional learning materials developed by teachers such as PowerPoint slides, explainer videos, and infographics. Interviews with three English teachers were also conducted. The result of the study showed that the microlearning features in each unit are not entirely satisfied, although numerous media have been found in a short amount of time, there are still certain components that have not been addressed. The study suggested that to improve students' writing English learning experiences, book writers and teachers should emphasize microlearning aspects and critical thinking skills more in learning materials.